Temporal trends in neonatal outcomes following iatrogenic preterm delivery - Joseph KS; Hutcheon Jennifer A; Lisonkova Sarka (BMC, 2011)
Abstract Background Preterm birth rates have increased substantially in the recent years mostly due to obstetric intervention. We studied the effects of increasing iatrogenic preterm birth on temporal trends in perinatal mortality and serious neonatal morbidity in the United States. Methods We used data on singleton and twin births in the United States, 1995-2005 (n = 36,399,333), to examine trends in stillbirths, neonatal deaths, and serious neonatal morbidity (5-minute Apgar ≤3, assisted ventilation ≥30 min and neonatal seizures). Preterm birth subtypes were identified using an algorithm that categorized live births <37 weeks into iatrogenic preterm births, births following premature rupture of membranes and spontaneous preterm births. Temporal changes were quantified using odds ratios (OR) and 95% confidence intervals (CI). Results Among singletons, preterm birth increased from 7.3 to 8.8 per 100 live births from 1995 to 2005, while iatrogenic preterm birth increased from 2.2 to 3.7 per 100 live births. Stillbirth rates declined from 3.4 to 3.0 per 1,000 total births from 1995-96 to 2004-05, and neonatal mortality rates declined from 2.4 to 2.1 per 1,000 live births. Temporal declines in neonatal mortality/morbidity were most pronounced at 34-36 weeks gestation and larger among iatrogenic preterm births (OR = 0.75, CI 0.73-0.77) than among spontaneous preterm births (OR = 0.82, CI 0.80-0.84); P < 0.001. Similar patterns were observed among twins, with some notable differences. Conclusion Increases in iatrogenic preterm birth have been accompanied by declines in perinatal mortality. The temporal decline in neonatal mortality/serious neonatal morbidity has been larger among iatrogenic preterm births as compared with spontaneous preterm births.